پیره‌مێردی چیرۆكنووس و زیندووكه‌ره‌وه‌ی په‌ندی پێشینان - به‌رزنجی, عثمان عبدول معروف (Sulaimani Journal for Humanities, 2023)
Piramerd is a poet, novelist, proverb collector and journalist of the first half of the twentieth century. This prominent figure after acquiring a great deal of knowledge and experiments in the field of journalism and different genera of literature in abroad, he got back home. He gave up working in governmental offices so as to boost the awareness of Kurdish citizens. He directed his attention to writing and publishing. Journalism, as one of his perpetual hobbies, became one of the factors of revealing his talents in writing. He exerted all his abilities and efforts in “Zheen” and “Zhiyan” to convey his messages through different literary genera. The goal and mission of Piramerd were clear and obvious. These were achieved by reflecting his world view, growth and development of his native language, culture, and literature through revitalization of the old generations and ancestors’ memories and proverbs. Since Piramerd was multilingual and experienced in the literature of other nations, particularly, Turkish, Persian and Arabic, he knew well the status of his nation’s literature. As the Kurdish people paid little attention to the written language and they focused on the spoken language instead, so many writers, poets and national heroes are lost and their names were forgotten. The study is an academic and scientific overview for piramerd’s stories, dramas and proverbs Which is very little comparing to the level of his poems, articles and proverbs. But it touches the periphery of the messages of piramerd to which he devoted his life.
Keywords: Story; proverbs; journalism; Drama